Curbing Money Politics: A Closed Proportional System For Indonesia’s 2029 Elections - Isyrofah Amaliyah Achmad (Dinasti Research, 2025)
Abstract: General elections, especially in the case of closed legislative elections, are a balanced representation system in which voters can only vote for political parties as a whole and cannot elect candidates (legislative candidates) who have been prepared directly by political parties, so voters cannot vote directly for the candidates. By law, voters can only vote for political parties participating in elections. The closed electoral system was used to implement elections in Indonesia, beginning with the New Order Election in 1955 and continuing until the 1999 Election. In the upcoming 2029 election year, it will likely use a closed proportional system by adjusting the provisions stipulated in Law Number 7 of 2017. The determination of regions' elections is part of the annex in the Election Law, so this becomes significant because the electoral district is regulated as a mandate in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia, which requires guarantees of legal certainty regarding matters regulated by law because of the role of the KPU, legislative candidates, political parties, and society. Implementing elections with a closed proportional system aims to prevent the occurrence of money politics because voters only need to choose the image of a political party on the election paper, and it will have a direct impact on each electoral district. Keyword: Democracy, Closed Proportional System, Money Politics, Electoral District, Effective Rule of Law.